An Intellectual Disability-Related Missense Mutation in Rac1 Prevents LTP Induction - Tian, Chen; Kay, Yuni; Sadybekov, Anastasiia; Rao, Sadhna; Katritch, Vsevolod; Herring, Bruce E. (Frontiers in Molecular Neuroscience, 2018)
The small GTPase Rac1 promotes actin polymerization and plays a critical and increasingly appreciated role in the development and plasticity of glutamatergic synapses. Growing evidence suggests that disruption of the Rac1 signaling pathway at glutamatergic synapses contributes to Autism Spectrum Disorder/Intellectual disability (ASD/ID)-related behaviors seen in animal models of ASD/ID. Rac1 has also been proposed as a strong candidate of convergence for many factors implicated in the development of ASD/ID. However, the effects of ASD/ID-related mutations in Rac1 itself in neurons have not been explored. Here we investigate a recently reported de novo missense mutation in Rac1 found in an individual with severe intellectual disability. Our modeling predicted that this mutation would strongly inhibit Rac1 activation by occluding Rac1’s GTP binding pocket. Indeed, we find that this de novo mutation prevents Rac1 function and results in a selective reduction in synaptic AMPA receptor expression. Additionally, this mutation prevents the induction of LTP, the cellular mechanism underlying learning and memory formation. Together, our findings strongly suggest that this mutation contributes to the development of intellectual disability in this individual. Furthermore, our research demonstrates the importance of Rac1 in synaptic function and plasticity and contributes to a growing body of evidence pointing to dysregulation of actin polymerization at glutamatergic synapses as a contributing factor to ASD/ID.